2021
DOI: 10.3390/pr9091482
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Treatment Efficiency and Lowering the Operating Costs of Electrochemical Advanced Oxidation Processes

Abstract: Electrochemical advanced oxidation processes (EAOP®) are promising technologies for the decentralized treatment of water and will be important elements in achieving a circular economy. To overcome the drawback of the high operational expenses of EAOP® systems, two novel reactors based on a next-generation boron-doped diamond (BDD) anode and a stainless steel cathode or a hydrogen-peroxide-generating gas diffusion electrode (GDE) are presented. This reactor design ensures the long-term stability of BDD anodes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 49 publications
(66 reference statements)
1
6
0
Order By: Relevance
“…In the study by Santos et al, 20 the same efficiency was reached (99.9%), but in the presence of 20 g l −1 NaCl and EC was 7.33 kWh kg phenol −1 . Similar result was achieved in a study by Muddemann et al 4 where EC was 103.02 kWh kg −1 with almost complete mineralization (>99% COD), using BDD anode and SS cathode, but with 9 g l −1 Na 2 SO 4 . Some studies have shown very high energy consumption as, for example, in the case of treatment of phenolic wastewaters from cashew-nut processing industry with BDD anode by applying 20 mA cm −2 .…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…In the study by Santos et al, 20 the same efficiency was reached (99.9%), but in the presence of 20 g l −1 NaCl and EC was 7.33 kWh kg phenol −1 . Similar result was achieved in a study by Muddemann et al 4 where EC was 103.02 kWh kg −1 with almost complete mineralization (>99% COD), using BDD anode and SS cathode, but with 9 g l −1 Na 2 SO 4 . Some studies have shown very high energy consumption as, for example, in the case of treatment of phenolic wastewaters from cashew-nut processing industry with BDD anode by applying 20 mA cm −2 .…”
Section: Resultssupporting
confidence: 89%
“…Similarly, Oliveira et al 19 showed high efficiency of Ti/RuO 2 -TiO 2 anode. However, BDD anode might have other advantages such as lifespan of up to 18 years, significantly reducing the cost of EO, as claimed by Muddemann et al 4 Energy consumption.-The lowest energy consumption (EC) was recorded in electrolyte NaCl, and was 116.6 kWh kg phenol −1 at E f 99.9% (Fig. 4).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…BCRs are one of the most applied gas-liquid and gas-liquid-solid multiphase reactors in industrial processes. They are characterized by many benefits such as easy operation, efficient mixing, high heat and mass-transfer rates, low maintenance costs, and low energy consumption [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…When the OEP of the anode is lower than the direct electron transfer potential of organic pollutants, the oxygen evolution reaction occurs first in the anode during the electrolysis (Rodriguez-Narvaez et al 2021). This reduces the rate of • OH generated and the current efficiency, and prolongs the electrolysis duration, resulting in higher energy consumption (Muddemann et al 2021). Therefore, the choice of anode material is extremely critical.…”
Section: Introductionmentioning
confidence: 99%